Factors of Difficulty for the Disability Students in Learning English - Dara Notia; Ali Akbarjono; Detti Lismayanti (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
The writing of this thesis is was motivated by the difficulty in learning English experienced by children with special needs, especially tunagrahita students, this is based on the limitations of their thinking abilities. Because tunagrahita students can be interpreted as mentally weak, brain weak, weak in mind, mentally disabled, or mental retardation. The purpose of this study was to describe the factors that influence the process of learning English faced by Mental Retardation students who were selected as research subjects. This research was conducted at the SLB Dharma Wanita Persatuan Provinsi Bengkulu, with five research subjects in ninth grade Tunagrahita coded with the initials MPS, IPH, VR, AS, and NA. This type of research is a qualitative descriptive analysis. The data collection technique used by conducting interviews and observations. The data analysis technique was carried out in 3 stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the factors that influenced the difficulty in learning English for Mental Retardation students at SLB Dharma Wanita Persatuan Provinsi Bengkulu were the influence of several factors including: (1) the method applied during learning (2) the teacher did not always use learning media, the media used was useless varied and less interesting so that students get bored easily; and the last is (3) the factors that exist in students, including physiological factors, cognitive factors, and fatigue factors.